Percutaneous Hepatic Perfusion With Filtered Melphalan for Localized Treatment of Metastatic Hepatic Disease: A Risk Assessment. (November 2018) - McEwan, Pauline E.; Bailey, Lynn; Trost, David; Scull, Christopher; Keating, John H.; Williams, Misty; Guttendorf, Robert J.
Regional therapies for metastatic liver disease have garnered interest in recent years due to technological advances in drug delivery. A percutaneous hepatic perfusion (PHP) using a newly developed generation 2 (GEN2) filtration system was designed to mitigate systemic toxicity and cardiovascular risk associated with hepatic blood filtration during hepatic artery infusion of the chemotherapy drug melphalan. The GEN2 system was evaluated in healthy swine, and plasma samples were assessed for clinical chemistry, melphalan toxicokinetics (TK), inflammatory cytokines, catecholamines, hematological, and cardiac biomarkers. Cardiovascular safety was assessed by echocardiography, electrocardiogram, and telemetry. Toxicology parameters included clinical signs, body weight, gross pathology, and histopathology. There were no treatment-related deaths associated with the PHP procedure with GEN2 filtration, and all animals survived to scheduled necropsy. Assessment of the pharmacokinetic/TK plasma concentrations of melphalan demonstrated that the GEN2 filter was able to extract melphalan from blood with high efficiency and reduce melphalan exposure in the systemic circulation. The hemodynamic, immunosuppressive, immunotoxic, cardiotoxic, and histopathologic effects of melphalan were limited. The significant hemodynamic challenge imposed by filtration resulted in a compensatory tachycardia with supranormal left ventricular function, although no wall motion abnormalities were detected and left ventricular function remained normal. Catecholamines decreased and then quickly rebounded during washout. Transient and reversible effects of treatment on cardiac enzymes, catecholamines, and cytokines and reversible hemodynamic effects without cardiac damage indicated that PHP with melphalan was not cardiotoxic or immunotoxic under the conditions tested, due to high efficiency of the filtration system limiting exposure of melphalan to the systemic circulation.